Sweet as honey, bitter as bile: Mitochondriotoxic peptides and other therapeutic proteins isolated from animal tissues, for dealing with mitochondrial apoptosis. (15th January 2021) - Colella, Francesco; Scillitani, Giovanni; Pierri, Ciro Leonardo
Abstract: Mitochondria are subcellular organelles involved in cell metabolism and cell life-cycle. Their role in apoptosis regulation makes them an interesting target of new drugs for dealing with cancer or rare diseases. Several peptides and proteins isolated from animal and plant sources are known for their therapeutic properties and have been tested on cancer cell-lines and xenograft murine models, highlighting their ability in inducing cell-death by triggering mitochondrial apoptosis. Some of those molecules have been even approved as drugs. Conversely, many other bioactive compounds are still under investigation for their proapoptotic properties. In this review we report about a group of peptides, isolated from animal venoms, with potential therapeutic properties related to their ability in triggering mitochondrial apoptosis. This class of compounds is known with different names, such as mitochondriotoxins or mitocans.